Restrictive Transfusion in Geriatric Trauma Patients. Issue 1 (January 2016) - Deleon, Ashley N.; Uecker, John M.; Stafford, Susan V.; Ali, Sadia; Clark, Adam; Brown, Carlos V. R.
To determine whether a restrictive strategy of red cell transfusion was safe in elderly trauma patients, we compared those treated with a restrictive transfusion strategy versus those who were liberally transfused. We performed a retrospective study of elderly (age ≥ 70 years) trauma patients admitted to our Level I trauma center from 2005 to 2013. Patients with a hemoglobin (Hg) < 10 g/dL after 48 hours were included. We excluded patients with an Injury Severity Score > 25 or active cardiac ischemia. Patients who were transfused for an Hg < 10 g/dL (liberal group) were compared to those who were transfused for an Hg< 7 g/dL (restrictive group). There were 382 patients included, 229 and 153 in the liberal and restrictive transfusion groups, respectively. All patients in the liberal group and 20 per cent of patients in the restrictive group received a transfusion ( P < 0.0001). Patients in the liberal group had more overall complications (52 vs 32%, P = 0.0001). On multivariate analysis, receiving a transfusion was an independent risk factor to develop a complication [odds ratio = 2.3 (1.5–3.6), P < 0.0001]. For survivors, patients in the liberal group spent more days in the hospital (nine versus seven days, P = 0.007) and intensive care unit (two versus one day, P = 0.01). There was no difference in mortality (3 vs 4%, P = 0.82). In conclusion, restrictive transfusion appears to be safe in elderly trauma patients and may be associated with decreased complications and shortened length of stay.